2019
DOI: 10.3389/fimmu.2019.01905
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Activity of Anti-interferon-γ Autoantibodies in Adult-Onset Immunodeficiency Is Associated With Their Binding Domains

Abstract: Adult-onset immunodeficiency (AOID) with anti-interferon-γ (IFN-γ) autoantibodies (autoAbs) is an emerging immunodeficiency syndrome in Asian countries. The presence of neutralizing anti-IFN-γ autoAbs are significantly associated with severe disseminated opportunistic infections. However, the characteristics of the neutralizing antibodies in patients are poorly defined. To better understand the properties of the anti-IFN-γ autoAbs in patients with opportunistic infections, a simplified competitive-binding ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…To understand the mechanisms underlying the pathogenesis of AOID better, anti-IFN-γ autoAbs from patients should be characterized. In our previous study, the autoAbs of patients with AOID recognized the same epitope as B27 mAb 12 . Since B27 mAb did not recognize the C-terminal epitope identified by Lin et al 11 , the epitope for a particular autoAb in patients with AOID was investigated further.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…To understand the mechanisms underlying the pathogenesis of AOID better, anti-IFN-γ autoAbs from patients should be characterized. In our previous study, the autoAbs of patients with AOID recognized the same epitope as B27 mAb 12 . Since B27 mAb did not recognize the C-terminal epitope identified by Lin et al 11 , the epitope for a particular autoAb in patients with AOID was investigated further.…”
Section: Discussionmentioning
confidence: 76%
“…However, the epitope recognized by the pathogenic autoAbs has not yet been thoroughly investigated. In a previous study, we had reported that autoAbs in patients with AOID competed with neutralizing mouse anti-IFN-γ monoclonal antibody (mAb) (clone B27) 12 . Epitope mapping using 20-mer synthetic peptides revealed that B27 mAb does not bind to the C-terminal epitope.…”
Section: Introductionmentioning
confidence: 99%
“…8 Commercially available mouse anti-IFN-c monoclonal antibodies can bind to distinct epitopes of the IFN-c molecule with different neutralizing activity. 22 Competitivebinding ELISA using commercial neutralizing mouse anti-IFN-c monoclonal antibodies showed that anti-IFN-c AAbs in patients bind to discontinuous epitope of homodimeric IFN-c. This study also demonstrated the heterogeneity of the auto Abs against IFN-c in AOID patients and the diverse patterns among individuals.…”
Section: Characteristics Of Anti-ifn-c Aabsmentioning
confidence: 99%
“…INF-ɣ is mainly produced by Th1 cells, the activation of its receptor (INF-ɣR) phosphorylates and activates molecules such as STAT1. [64] Some studies have shown that the ability of interferon inhibition by these autoantibodies is more important than the concentration to determine the predisposition to the disease, besides there is a heterogeneity between the types of autoantibodies in each individual [65] [66].…”
Section: Adul-onset Immunodeficiency With Susceptibility To Mycobacteriamentioning
confidence: 99%